Bond Strength to Microtraction and Nanofiltration Using Ethanol Wet Bonding Technique in Fresh Extracted Teeth: An Ex Vivo Study - Caceres, Sheyla (J Int Soc Prev Community Dent, 2020)
OBJECTIVE: The objective of this study was to evaluate the bond strength to microtraction and nanofiltration using ethanol wet bonding technique in fresh extracted teeth. MATERIALS AND METHODS: This quasi-experimental ex vivo study evaluated 48 teeth that had an indication of premolar extraction due to orthodontic reasons. The protocol of dental preparation and restorative procedure was carried out to evaluate the adhesion resistance by means of the universal testing machine at a loading speed of 0.5 mm/min and 500MPa. To evaluate the nanofiltration, matches were made that were immersed in ammoniac silver nitrate for 24h, and then the specimens impregnated with silver were washed thoroughly in distilled water and placed in a photo-developer solution for 8h under a fluorescent light. All statistical analyses were statistically evaluated with a level of significance P < 0.05. RESULTS: The ethanol technique without premature failure (PF) group had an average of 31.26 ± 10.26MPa, whereas the lowest value was found in the water technique group with PF, which had 22.59 ± 12.27MPa. When performing inferential statistics, it was evidenced that there were statistically significant differences between both techniques with a value of P < 0.05. CONCLUSION: According to the results in both cases, the adhesive strength showed superiority in the ethanol wash group. It determines that this technique presents greater tolerance to the residual presence of water. Finally, in relation to nanofiltration we found that there were no significant differences between the groups evaluated.